Phytoremediation potential of Vetiver system technology for improving the quality of palm oil mill effluent - Darajeh, Negisa; Idris, Azni; Truong, Paul; Abdul Aziz, Astimar; Abu Bakar, Rosenani; Che Man, Hasfalina (Hindawi Publishing Corporation, 2014)
Palm oil mill effluent (POME), a pollutant produced by the palm oil industry, was treated by the Vetiver system technology (VST). This technology was applied for the first time to treat POME in order to decrease biochemical oxygen demand (BOD) and chemical oxygen demand (COD). In this study, two different concentrations of POME (low and high) were treated with Vetiver plants for 2 weeks. The results showed that Vetiver was able to reduce the BOD up to 90% in low concentration POME and 60% in high concentration POME, while control sets (without plant) only was able to reduce 15% of BOD. The COD reduction was 94% in low concentration POME and 39% in high concentration POME, while control just shows reduction of 12%. Morphologically, maximum root and shoot lengths were 70 cm, the number of tillers and leaves was 344 and 86, and biomass production was 4.1 kg m−2. These results showed that VST was effective in reducing BOD and COD in POME. The treatment in low concentration was superior to the high concentration. Furthermore, biomass of plant can be considered as a promising raw material for biofuel production while high amount of biomass was generated in low concentration of POME.